Legal Analysis of Notary's Obligations in Reporting Suspicious Financial Transactions Based on the Principle of Recognizing Service Users in the Establishment of a Limited Liability Company - Sasmita Sarip, Cicilia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Notaries in their profession have obligations that must be obeyed. These notary obligations are stated in Article 16 of the UUJN. One of the notary's obligations is to keep confidential everything regarding the Deed they have made and all information obtained for the purpose of making the Deed. Based on PP No. 43 of 2015 concerning the Reporting Party in the Prevention and Eradication of Money Laundering Crimes, it adds to the obligations of Notaries as reporting parties. This Government Regulation requires notaries to report to the PPATK (Financial Transaction Reports and Analysis Center), regarding suspected money laundering crimes on deeds made by or before a notary as a public official. Notaries as reporting parties are required to implement the Principle of Recognizing Service Users (PMPJ). The method used by the researcher is normative juridical with a statutory approach. The specifications of this study are prescriptive. The type of data used is secondary data sourced from materials obtained from literature studies. Based on the results of the study that 1) Legal implications for the Obligations of notaries as reporting parties who report suspicious financial transactions are regulated in PP Number 43 of 2015, which is a derivative regulation of Law Number 8 of 2010 concerning the Eradication and Prevention of Money Laundering Crimes, adding notary obligations outside the obligations that have been regulated in the Notary Law. This is contrary to the law and triggers a dilemma in terms of its implementation and does not provide legal certainty. 2) Legal protection for notaries as reporting parties who report suspicious financial transactions based on the principle of recognizing service users for the establishment of a limited liability company aims to protect notaries as well as prevent the problem of money laundering crimes, especially those related to the preparation of the deed of establishment of a Limited Liability Company. Violation of these obligations can result in administrative sanctions based on the provisions of the Notary Law and the Eradication and Prevention of Money Laundering Law and its derivative regulations.